2023
DOI: 10.2196/45002
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and Members of the Public’s Wishes Regarding Transparency in the Context of Secondary Use of Health Data: Scoping Review

Abstract: Background Secondary use of health data has reached unequaled potential to improve health systems governance, knowledge, and clinical care. Transparency regarding this secondary use is frequently cited as necessary to address deficits in trust and conditional support and to increase patient awareness. Objective We aimed to review the current published literature to identify different stakeholders’ perspectives and recommendations on what information pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 206 publications
0
4
0
Order By: Relevance
“…In Canada, in 2019, respondents had mixed and more negative reactions when there was private sector involvement regarding research based on linked administrative health data [55]. In 2023, a review of the literature found that patients generally expect high transparency and have high concerns about sharing their data with private sector entities [56]. According to our results, Polish society trusts doctors and scientists the most.…”
Section: Public Trust For Research Using Biological Materials and Bio...mentioning
confidence: 72%
“…In Canada, in 2019, respondents had mixed and more negative reactions when there was private sector involvement regarding research based on linked administrative health data [55]. In 2023, a review of the literature found that patients generally expect high transparency and have high concerns about sharing their data with private sector entities [56]. According to our results, Polish society trusts doctors and scientists the most.…”
Section: Public Trust For Research Using Biological Materials and Bio...mentioning
confidence: 72%
“…(4) In the opt-out scenario, patients' informational rights are infringed, for their data are used for other purposes than their individual treatment without explicitly asking them for consent and without them explicitly giving their consent. However, the infringement is rather low if appropriate measures are taken, such as: information is broadly offered to patients 50 ; patients have the opportunity to have individual consultations with professional staff like physicians or study nurses if they wish; patients have very lowthreshold opt-out options (or multi-tiered opt-out options); other control rights are also warranted; an effective and comprehensive data protection governance framework is in place. As the opt-out scenario of SeConts implies a slight infringement of patients' informational rights, physicians supporting SeConts in the opt-out scenario would not fully respect these rights and thus not fully comply with their pertaining professional duties towards their patients.…”
Section: Physicians' Duty To Respect Patients' Informational Rightsmentioning
confidence: 99%
“…Increasingly, the term "health data social licence" is being used to describe which datarelated activities members of the public support, and under what conditions [18,33]. For example, the use of patient data for commercial and profit purposes is considered to be outside of social licence by some people based on multiple studies that identify it as problematic [18,21,22,24,27,34].…”
Section: Introductionmentioning
confidence: 99%
“…Public/patient participants: A total of 20 Canadian participants (10 English speaking and 10 French speaking) took part in the process (Table 1 -inline). Previous studies have reported that health data sharing, linkage, use, and reuse is a complex topic that is not well understood by members of the general public [18,34]. Therefore, recruitment focused exclusively on people who had prior experience as public or patient advisors in a health-related field and/or working with health data, e.g., in community organisations, hospitals, or health research institutes with the hope that such participants would be well-positioned to engage in dialogue with each other without extensive pre-reading or background preparation.…”
Section: Introductionmentioning
confidence: 99%